THE MEANING OF SLOGAN AND ERROR OF INDONESIAN LANGUAGE ON BEVERAGE ADVERTISEMENT ON TELEVISION - Setiawan, Kodrat Eko Putro (English Department FBS UNP, 2018)
The language error are often found in advertising slogan on television. The purpose of this study was to describe the meaning of Indonesian slogan and mistakes in advertisement of tea and coffee on television. The method used in this research is qualitative descriptive. Data sources in this study are words derived from the slogan of advertising in 2018 for tea and coffee drinks on INDOSIAR, RCTI, SCTV, MNC TV, ANTV, GLOBAL TV stations. Data collection techniques in this study are referenced and recorded. Data analysis in this study includes the interpretation of the meaning of the tea and coffee drink advertising slogan and the Indonesian language error contained in it. The results of this study are the meaning contained in the slogan of the advertisement of tea and coffee drinks on television showing that the advertising slogan makers display the superiority of their products in term of taste, product origin and health. Indonesian language error in the slogan of advertising for tea and coffee drinks on television include the use of foreign terms, the use of comma, elimination of conjunctions in clauses, improper use of prepositions, excessive use of elements, ambiguity of sentence, illogical sentence, non-parallel sequences, sentence that are not subject, words of affirmation, and influence of regional language.Keywords: meaning, slogan, television, advertisement, language errorMAKNA SLOGAN DAN KESALAHAN BERBAHASA INDONESIA PADA IKLAN MINUMAN DI TELEVISIAbstrakKesalahan berbahasa sering ditemukan dalam slogan iklan di televisi. Tujuan penelitian ini adalah mendeskripsikan makna slogan dan kesalahan berbahasa Indonesia dalam slogan iklan minuman teh dan kopi di televisi. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Sumber data dalam penelitian ini adalah kata-kata yang berasal dari slogan iklan minuman teh dan kopi di stasiun televisi INDOSIAR, RCTI, SCTV, MNC TV, ANTV dan GLOBAL TV tahun 2018. Teknik pengumpulan data dalam penelitian ini adalah simak dan catat. Analisis data penelitian ini meliputi interpretasi makna slogan iklan minuman teh dan kopi, serta kesalahan berbahasa Indonesia yang ada di dalamnya. Hasil penelitian ini adalah makna yang terkandung dalam slogan iklan minuman teh dan kopi di televisi menunjukkan bahwa pembuat slogan iklan menampilkan keunggulan produknya dari sisi rasa, asal usul produk dan kesehatan. Kesalahan berbahasa Indonesia dalam slogan iklan minuman teh dan kopi di televisi meliputi penggunaan istilah asing, penggunaan tanda koma, penghilangan konjungsi pada anak kalimat, pemakaian preposisi yang tidak tepat, penggunaan unsur yang berlebihan, ambiguitas kalimat, kalimat yang tidak logis, urutan yang tidak paralel, kalimat tidak bersubjek, kata imbuhan, dan pengaruh bahasa daerah.Kata kunci: makna, slogan, televisi, iklan, kesalahan berbahasaÂ Â